2013
DOI: 10.1007/s10877-013-9512-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hypotension in the beach chair position during shoulder arthroscopy using pre-operative hemodynamic variables

Abstract: Since hypotension in beach chair position (BCP) can lead to catastrophic neurologic complications, the prediction of hypotension is a matter of concern in the BCP under general anesthesia. We investigated whether pre-induction values of mean arterial pressure (MAP), stroke volume variation (SVV), cardiac index (CI), and stroke volume index (SVI) can predict hypotension in BCP during general anesthesia. Forty healthy adult patients, aged 18-65 years, undergoing elective arthroscopic shoulder surgery, were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
0
20
2
1
Order By: Relevance
“…Sufentanil lowers HR mainly through vagal nerve stimulation via the central nervous system, while propofol does not have prominent effects on HR 3,17 . Cisatracurium besilate at clinical doses has little effect on the cardiovascular system 18 There are many methods used to predict post-IGA hypotension, including cardiac index, stroke volume index, post-induction stroke volume variation, HR variability [19][20] , and perfusion variation index 1 . The IVC ci can reportedly predict the occurrence of post-IGA hypotension in a relatively accurate way 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil lowers HR mainly through vagal nerve stimulation via the central nervous system, while propofol does not have prominent effects on HR 3,17 . Cisatracurium besilate at clinical doses has little effect on the cardiovascular system 18 There are many methods used to predict post-IGA hypotension, including cardiac index, stroke volume index, post-induction stroke volume variation, HR variability [19][20] , and perfusion variation index 1 . The IVC ci can reportedly predict the occurrence of post-IGA hypotension in a relatively accurate way 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In the April issue, Yi Jo and colleagues investigated the big issue of hypotension associated with the beach chair position (BCP) during general anesthesia in forty healthy adult patients undergoing elective arthroscopic shoulder surgery [1]. Indeed, although fluid preloading with crystalloid or colloid fluids may alleviate the hemodynamic consequences associated with the BCP during general anesthesia, the present fluid therapy may possibly lead to volume overload.…”
Section: Evaluation Of Haemodynamic Alterations and Fluid Responsivenessmentioning
confidence: 99%
“…Indeed, although fluid preloading with crystalloid or colloid fluids may alleviate the hemodynamic consequences associated with the BCP during general anesthesia, the present fluid therapy may possibly lead to volume overload. In this regard, the authors investigated whether hemodynamic variables obtained using the FloTrac/Vigileo system, including mean arterial pressure and stroke volume variations (SVV) could predict hypotension in mechanically ventilated patients undergoing BCP [1]. Hypotension related to the BCP posture occurred in 37.5 % of patients in this study and the authors found that in contrast to post-induction value of SVV in mechanically ventilated state, pre-induction SVV cannot predict hypotension associated with the BCP in this study [1].…”
Section: Evaluation Of Haemodynamic Alterations and Fluid Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Um auch bei dieser Lagerung eine ausreichende Perfusion des Gehirns zu gewährleisten, bedarf es einer engmaschigen Kontrolle des Blutdrucks. Bei Risikopatienten wird die Indikation zur Etablierung einer invasiven Blutdruckmessung mit erweitertem hämodynamischem Monitoring daher meist großzügiger gestellt[27]. Abb.…”
unclassified